Comparative study of using thiopentone sodium –ketamine– chloral hydrate mixture and ketamine– chloral hydrate mixture as a general anesthetics in local pigeons - Khutair, Napeel abdul Al-Rahman (The Iraqi Journal of Veterinary Medicine, 2009)
This study aimed to use two kinds of mixtures of general anesthetics to know which is betterfrom induction of anesthesia and anesthesia period and their effect of some essential parameters inanesthesia like temperature, pulse, and respiration.Twenty birds of local pigeons were selected then devided into two groups.The first group treatedwith thiopentone sodium –ketamine–chloral hydrate mixture , other group treated with –ketamine–chloral hydrate mixture